QUANTIFICATION OF ρ (pera) - METHOXY CINNAMIC ACID ETHYL ESTER (PMCAEE) FROM HEDYCHIUM SPICATUM BY HPTLC - ARORA RITU,; JAIN SHIPRA, (International Journal of Pharma and Bio Sciences, 2010)
Hedychium spicatum Ham (Zingiberaceae), is an aromatic annual herb, which is used in Traditional System of Medicine to treat various diseases like like antimicrobial, antidiabetic, pediculicidal and antioxidant. The reported constituents are flavonoids, glycosides and saponins. From literature it was found that the quantification work was not carried out. It is considered to contain ρ -methoxy cinnamic acid ethyl ester (PMCAEE) confirmed by TLC and by qualitative test. Thus it was quantified using HPTLC a sensitive method for development of marker compounds. The method was carried out on precoated TLC aluminum plates with silica gel 60 F254 as stationary phase using solvent system as Hexane: Acetone(80:20 v/v). with Rf value of 0.43. Quantitative analysis was carried out in the absorbance at 310 nm. The linearity regression for the calibration showed r = 0.6548 and 0.999 with respect to height and area in a range of 0.5-5.0 g per spot. Thus HPTLC method provides a faster and cost effective quality control for the routine analysis of PMCAEE in extracts containing Hedychium spicatum..